PEMANFAATAN BELIMBING WULUH (AVERRHOA BILIMBI L) SEBAGAI BIOKOAGULAN LIMBAH LIMING - Rohmatun Wahyuni; Khurriyatul Khasanah; Joko Samiyo; RLMS Ari Wibowo (Politeknik ATK Yogyakarta, 2013)
In many industry, water purification methods like flocculation and coagulation are often inappropriate because of the high cost and low availabity of chemical coagulants. The concern for environmental and ecological issues encaurages the use of the biodegradable coagulant int waste water and industrial effluent treatment. Biocoagulant from Averrhoa Bilimbi fruits are alternatived because can precipitate the lime, especially for easily handling and more economical alternative in countries where the plant are available. This biocoagulant has been investigated to treat water effluent from limming processes. A series of jar test were conducted to determine the parameter involved during coagulation flocculation prosses. The treatment by adding 25 ml dosage of Averrhoa Bilimbi biocoagulant and with the addition of 10 drops of aquaclear as flocculants in wastewater liming the natural wastewater at pH 12.00, 0.17 unit decreasing of pH ,resulted 91 NTU turbidity reduction, resulted 0.008% and 0.0117 grNa2S levels of lime and sulphide reduction.